The Role and Legal Responsibilities of Directors and Commissioners in Facing Administrative, Criminal and Civil Risks - Indra Utama Tanjung; Vivian Alyssa Chandra; Khania Amanda Salsabila; Ryan Fahri Rangkuti; Aufiya Muhammad Syukri Al Ghiffary (Jurnal Cendikia ISNU SU, 2024)
This article examines the roles and legal responsibilities of directors and commissioners in corporate law, particularly regarding administrative, criminal, and civil risks. Directors, as the managing body, and commissioners, as supervisors, have legal obligations inherent in their strategic functions. In the Indonesian legal system, violations of the principles of prudence and good faith can give rise to personal liability. This study uses a normative juridical approach by analyzing relevant laws and regulations and jurisprudence. The results of the study indicate that there is still a lack of clarity in the application of accountability standards, particularly in distinguishing between corporate and individual management responsibilities. This lack of clarity can create legal uncertainty and risks for company managers. Therefore, this article recommends updating legal norms and strengthening the principles of good corporate governance as preventive measures to clarify the boundaries of responsibility and minimize legal risks for directors and commissioners.